The Relationship "WASH" Educational to Farmers in Agrarian Regions: COVID-19 Prevention - Yarmaliza, Yarmaliza; Nih Farisni, Teungku; Fitriani, Fitriani; Zakiyuddin, Zakiyuddin; Reynaldi, Fitrah; Nella Syahputri, Veni (International Journal of Social Science, Education, Communication and Economics, 2022)
This research uses Pre-Experimental Design without control group with One Group Pretest-Posttest Design. The study was conducted in March 2021 in two districts that were confirmed to be inhabited by COVID-19 positive residents (Johan Pahlawan District and Meureubo District), West Aceh, Indonesia. Statistical analysis used: Hand-washing is one way to prevent COVID-19 transmission. This is essential because in this global pandemic, every community has the opportunity to catch COVID 19. The research objective was to determine the effectiveness of WASH educational collaboration on farmers as an attempt to COVID-19 prevention. The population in the study is all farmers who live in these mentioned districts. There were 37 farmers in total. The sampling method used total sampling, namely 37 farmers who live in the areas that are confirmed to have positive patients of COVID 19. Data were analyzed using Univariate, Bivariate (Dependent T-test) and Multivariate with using logistic regression. The result shows that there is a significant influence between the collaboration of WASH Education on farmers as an effort to prevent COVID-19 with a statistical test value of P-Value <0.05. Collaboration on WASH education for farmers is very influential in preventing COVID-19. It is hoped that cross-sectoral involvement and roles can be maintained so that COVID 19 prevention behavior through WASH can continue to be applied. Educative collaboration of WASH impacts on the behaviour alteration toward farmers who live in the area confirmed to be infected by COVID 19.